pedagogy of the body in the MA Project, a holistic perspective in health communication and social change: Una perspectiva integral en comunicación para la salud y el cambio social - Novella Centellas, Carolina (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
The Ma Project, my body my house (Colombia) is an education through dance intervention that, in a context of extreme poverty, violence and social inequity, aims to restore the value of the individual and the social body. This article introduces partial results from a qualitative research about the Project and examines them from a health perspective. Through participatory and ethnographic techniques the study analyzes the project and the perceived influence in individuals and the community. The main results indicate that the Project introduces silence and corporeal work as communicative elements of an integrative pedagogy that will generate transformations based on respect. This case study illustrates how through an integral approach to communication that incorporates cultural elements and social relations, individual and social transformations occur. These changes will affect not only the health conditions of the participants but also their living conditions.